Infant feeding practice and associated factors of HIV positive mothers attending prevention of mother to child transmission and antiretroviral therapy clinics in Gondar Town health institutions, Northwest Ethiopia - Muluye Dagnachew; Woldeyohannes Desalegn; Gizachew Mucheye; Tiruneh Moges (BMC, 2012)
Abstract Background It has been estimated that 430,000 children under 15 years of age were newly infected with HIV in 2008, and more than 71% are living in sub-Saharan Africa. In the absence of intervention to prevent mother-to-child transmission, 30-45% of infants born to HIV-positive mothers in developing countries become infected during pregnancy, delivery and breastfeeding. The aim of this study was to assess infant feeding practice and associated factors of HIV positive mothers attending prevention of mother to child transmission and antiretroviral therapy clinics of Northwest Ethiopia. Methods Institution based cross sectional study was conducted from January to May 2011 among all HIV positive mothers with less than two years old child attending prevention of mother to child transmission and antiretroviral therapy clinics in Gondar Town health institutions. A structured pre-tested questionnaire using interview technique was used for data collection. The data was entered and analyzed using SPSS version 16 statistical package. Results A total of 209 HIV positive mothers were included in the study. Of these, 187 (89.5%) had followed the recommended way of infant feeding practice while significant percentage (10.5%) had practiced mixed breast feeding. In multivariate analysis, disclosure of HIV status with their spouse, insufficient breast milk and occupational status were found to be independently associated (p-value of < 0.05) with recommended infant feeding practice. Lack of resource, stigma of HIV/AIDS, and husband opposition were also obtained as factors that influenced choice of infant feeding options by respondents. Conclusions Higher proportion of respondents used the recommended way of infant feeding practice by WHO as well as by Ethiopian Ministry of Health. However, mixed feeding in the first 6 months of age, an undesirable practice in infant feeding, were reported in this study. Infant feeding education that is aligned to national policy should be strengthened in primary health care, particularly in situations where prevention of mother to child transmission of HIV is prioritized.